Strategi Bertahan Hidup Ojek Online di Kota Surabaya Pada Masa Pandemi Covid-19 (Studi Kasus di Raya Mulyosari) - prakoso, aldo elang; Setyawan, Katon Galih (Paradigma, 2023)
This research discusses the survival strategies of online motorcycle drivers in the city of Surabaya during the Covid 19 pandemic. The aim of this research is to understand the family and economic survival strategies of online motorcycle drivers during a pandemic and to find out the function of the strategy of online motorcycle drivers. used to survive or not. The research method uses descriptive qualitative. Data collection techniques were carried out by means of observation, interviews and documentation. The concept used in this study is the survival strategy of James C. Scoot. The results of this study are that during the Covid 19 Pandemic, were online motorcycle drivers able to meet their daily needs so that online motorcycle taxi drivers had to apply several strategies to survive such as implementing active strategies, passive strategies and network strategies.